Critical Thinking Skills of Mathematics Prospective Teachers: An Exploration Study at Medan State University. (February 2020) - Firdaus, M; Mukhtar,
Abstract: This study aims to examine mathematics prospective teachers' critical thinking skills at mathematics education program, Medan State University. This research is intended to contribute to the program to improve the professionalism of prospective mathematics teachers in critical thinking, one of the important skills in the 21st century. The results of this study will be the basis for further action in developing a learning models with reference to the current status of math prospective teachers' critical thinking skills. In this study, data analysis was carried out through quantitative analysis. The Watson and Glaser Critical Thinking Appraisal in the Indonesian version was administered for data collection. Data was collected from 165 prospective teachers during the first semester of the 2019-2020 academic year. The results showed that prospective teachers' critical thinking grades are in average level. Therefore, further studies must be carried out to identify and overcome deficiencies, to enhance critical thinking in math prospective teacher students.